Climate Change and its Impact on Asian Forest Landscapes: A Critical Review - Rakuasa, Heinrich; Latue, Philia Christi; Pakniany, Yamres (Journal of Selvicoltura Asean, 2024)
The impact of climate change on Asian forests is significant because it can affect temperature, rainfall, forest growth, seasonal patterns, and ecosystem balance. The research method used is a literature study that includes analyzing historical data, current observations, and monitoring climate change trends in the Asian region. The results show that climate change has led to an increase in average temperatures, changes in rainfall patterns, and melting of glaciers and ice in the Asian mountains. These impacts extend to various aspects of life, including ecosystems, agriculture, human well-being, and natural resource availability. Therefore, comprehensive mitigation and adaptation strategies and international cooperation are needed to protect Asia’s forest ecosystems and increase people’s resilience to the impacts of climate change.